An overview on the use of additives and preparation procedure in phase change materials for thermal energy storage with a focus on long term applications. (September 2022) - Ribezzo, Alessandro; Falciani, Gabriele; Bergamasco, Luca; Fasano, Matteo; Chiavazzo, Eliodoro
Abstract: In this review we aim at providing an up-to-date and comprehensive overview on the use of additives within selected Phase Change Materials (PCMs) from both an experimental and more theoretical perspective. Traditionally, mostly focusing on short-term thermal energy storage applications, the addition of (nano)fillers has been extensively studied to enhance unsatisfactory thermo-physical properties in PCMs, in order to overcome limiting aspects such as low thermal conductivity possibly leading to unacceptable long charging and/or discharging periods and inefficient heat-storage systems. On the other hand, here we focus on the most important PCMs for long-term thermal energy storage (i.e. spanning from classical solid-to-liquid to more recent solid-to-solid PCMs) and make an effort in shedding light on the role played not only by additives but also (and importantly) by additivation protocols on the resulting thermo-physical and stability properties. While introducing and connecting to general advantages related to additivation in classical PCMs for thermal energy storage, we discuss specifically the use of additives in sugar alcohols and sodium acetate trihydrate, as well as in novel emerging classes of PCMs capable of undergoing solid-to-solid transitions and showing promising features for long-term heat storage materials. We highlight outstanding issues in the use of additives for property enhancement in PCMs and expect that the present work can contribute to expand the current understanding and field of application of the less mature PCMs for thermal energy storage, especially as far as long term applications are concerned. Highlights: Impact of additives and preparation procedures on selected PCMs for heat storage. Stability and properties in SAT and sugar alcohols for long-term heat storage. Enhancement of plastic crystals and solid-to-solid PCMs materials for energy storage.